Relationships between extension policies, planning, language of communication and achievement of extension services delivered to crop farmers in North-Eastern Nigeria - Abubakar, Shehu Umar (2022)
The slow growth of agriculture and food production is evident in the growing food importation, with eminent non-sustainability, increased threat of food insecurity, commerce, and trade. Against this backdrop, this study was designed to gauge the effectiveness of extension services among food crop farmers in North eastern Nigeria. Extension policies enable farmers to learn the latest expertise and to introduce the latest technology to increase the productivity of the agricultural sector. According to Gambo (2017), extension workers face difficulties in delivering their extension services to crop farmers due to the fact that some of the extension agents could not speak the language of the farmers. Therefore, this study will help to give a clear picture of the relationships between extension policies, planning, and language of communication on achievement of extension services. The research frame work of this study was developed based on four (4) model theories which include Achievement Motivation Theory (AMT), Policy theory, Theory of Strategic Planning, as well as Classical Communication Model. Six states were selected from North-east Nigeria consisting of Adamawa, Bauchi, Borno, Gombe, Taraba and Yobe with a total population of about 18,984,299 and with divers’ tribes. The population of the study in this research comprises of 3300 registered crop farmers and 356 registered crop farmers were randomly selected proportionately. A well-structured five-point Likert scale questionnaire was reviewed and pre-tested for its validity and reliability. The study employed a descriptive, correlation and multiple regression models to analyze and compute the data using SPSS version 21. Results of the demographic profile showed that (87.10%) of the respondents involved are male within the age range 26 and 35 years. In total, 45.5% of the populations are Hausa. About 5.9 percent had primary school education; (54.8%) had secondary school education; the college/university education of the respondents had (33.4%); a fourth (5.9%) did not indicate their level of education. Most (63.5%) of the respondents were engaged in crop production. The study revealed that extension activities had high impact on improving sequence of planning extension activities on crop farmers having high percentage of 57.3 % with (M=3.82, SD=±0.59) and also on direction of planning had a medium impact of extension services on crop farmers at 49.7 % (M=3.74, SD=±0.72). The scope of planning was highly impacted to the crop farmers by the extension workers based on the available information with 54.5% and at (M=3.67, SD=±0.80). Majority of the farmers interviewed (55.9%, (n = 199) with (M=3.49, SD=±0.77) said that extension agents had fluency in language of thought at their local areas. The relationship between policies, planning and language was positive and highly significant (p<0.05) among the crop farmers on achievement of extension services. Language of communication recorded the strongest (r = 0.739) relationship. The cause-effect relationship between the variables further showed that policies and language of communication significantly (p<0.05) affected achievement of extension services among crop farmers. The regression model was significant with an R-value 0.755. In this respect, the current study showed that the relationship between the factors (policies and language of communication) indicates a significant impact on the achievement of extension services among crop farmers in North-Eastern Nigeria. Government agencies should therefore train and send extension workers that understand the language of crop farmers for effective message deliverance. Crop farmers should be made aware on the importance of government policies and plans on new technologies to improve agricultural activities